Research on Curvilinear Motion of Automobile with the Application of On-Board Can Bus Data - Hubert Sar; Mateusz Brukalski; Krzysztof Rokicki (Communications - Scientific letters of the University of Zilina, 2021)
Modelling of vehicle’s motion is one of the solutions applied in the research of automotive safety. There is always a discussion which model should be used for computer simulation. Models with higher number of degrees of freedom require identification of many parameters, which are usually difficult to obtain. So, very often relatively simple flat model of vehicle’s motion is applied. It needs only such parameters as mass of a vehicle, location of centre of gravity from front and rear axle, yaw mass moment of inertia and side slip characteristics of the front and rear axle. In this paper the upper mentioned model was applied, considering different side slip characteristics of the front and rear axle. The scenario of vehicle’s motion was based on random changes of steering wheel angle during the road test, recording signals from on-board CAN (Controller Area Network) bus of automobile simultaneously, which were further applied in simulation.